Psychometric properties of the formative assessment test for the statistics course - Helli Ihsan; Wardani Rahayu; Riyan Arthur (Inovasi Kurikulum, 2026)
This study is motivated by the importance of formative assessment in enhancing students’ understanding and engagement in Psychological Statistics learning, as well as the limited availability of psychometrically sound instruments. The study aims to develop a structured formative assessment instrument that is valid and reliable, and to analyze item characteristics using Classical Test Theory (CTT) and Item Response Theory (IRT). This research employed an instrument development design involving 191 first-year psychology students. The initial instrument consisted of 40 multiple-choice items constructed based on learning outcomes and validated through expert judgment using Aiken’s V. Data analysis was conducted in stages, including item-total correlation analysis, IRT 1PL for item difficulty, and IRT 2PL for both difficulty and discrimination parameters. The results showed that after the selection process, 29 items met the psychometric criteria, with difficulty levels predominantly in the easy-to-moderate range, good discrimination indices, and high reliability. These findings indicate that the developed instrument accurately and consistently measures students’ understanding and can be effectively used as a formative assessment tool to support statistics learning in higher education.   Penelitian ini dilatarbelakangi oleh pentingnya asesmen formatif dalam meningkatkan pemahaman dan keterlibatan mahasiswa pada pembelajaran Statistik Psikologi, serta keterbatasan ketersediaan instrumen yang memiliki kualitas psikometris yang teruji. Penelitian ini bertujuan untuk mengembangkan instrumen asesmen formatif terstruktur yang valid dan reliabel, serta menganalisis karakteristik butir menggunakan pendekatan Classical Test Theory (CTT) dan Item Response Theory (IRT). Metode yang digunakan adalah penelitian pengembangan instrumen dengan melibatkan 191 mahasiswa semester pertama Program Studi Psikologi. Instrumen awal terdiri dari 40 butir soal pilihan ganda yang disusun berdasarkan capaian pembelajaran dan divalidasi melalui expert judgment menggunakan Aiken’s V. Analisis data dilakukan secara bertahap melalui uji korelasi item-total, analisis IRT 1PL untuk parameter kesulitan, serta IRT 2PL untuk parameter kesulitan dan daya diskriminasi. Hasil penelitian menunjukkan bahwa setelah proses seleksi, diperoleh 29 butir soal yang memenuhi kriteria psikometris dengan tingkat kesulitan yang dominan mudah hingga sedang, daya diskriminasi yang baik, serta reliabilitas yang tinggi. Temuan ini menunjukkan bahwa instrumen yang dikembangkan mampu mengukur pemahaman mahasiswa secara akurat dan konsisten, serta dapat digunakan sebagai alat asesmen formatif yang efektif untuk mendukung pembelajaran statistik di pendidikan tinggi. Kata Kunci: asesmen formatif; classical test theory; item response theory; statistik psikologi